KINERJA AGREGAT ALAM UNTUK BETON MUTU TINGGI - Mallisa, Harun (MEKTEK, 2009)
Nowadays, concrete construction even it small, medium and large scale; normally use natural sand (sand river) as fine aggregate and artificial aggregate from crushed stone as coarse aggregate; and it is rarely found concrete mix which consist of both natural fine and coarse aggregates because bond capacity between natural coarse aggregate and cement paste lower than between artificial coarse aggregate and cement paste.This research aims to know the performance of natural coarse aggregate, which was used for high performance concrete (HPC) with use admixture. Tests were carried out by using specimens of concrete cube with size of 15 cm x 15 cm x 15 cm and vary of water cement ratio and percentage of admixture CONPLAST SP – 420 using both natural and artificial coarse aggregate.The results of this research show that although natural coarse aggregate replaced by 50 % with artificial coarse aggregate; the resulted concrete compression strength not too significant compare to concrete mix use natural coarse aggregate; furthermore, replace 50 % artificial coarse aggregate with natural aggregate can reduce the cost of concrete production